Reconciliation reconstruction and development as paradigms for missiology in South Africa : a reading of David Bosch's paradigms for Missiology - Niemandt, Cornelius Johannes Petrus (Nelus) (University of Pretoria, 2018)
PhD. In Missiology by Rev Victor Vythalingum Pillay, supervised by Prof C J P (Nelus) Niemandt, in the Department of Science of Religion and Missiology in the Faculty of Theology at the University of Pretoria. The title of the thesis “Reconciliation, Reconstruction and Development as Paradigms for Missiology” – A Reading of Prof David Bosch Paradigms in Missiology. The study deals with addressing the need for relevant paradigms for a missional approach to the needs and challenges to a post-1994 South Africa. Bosch’s introduction of paradigms to the discipline of missiology was a ground breaking academic exercise. In order to deal with this challenge, the researcher embarked on a Pastoral Cycle approach. Here one starts the discussion with the issue of Faith. Then the discussion and dialogue moves on to the theological aspects of Insertion, Social Analysis, Theological Analysis, Theological Reflection, Spiritual Formation and Empowerment and Pastoral Planning and Praxis. Through these points of reflection, the academic journey proceeds. The publication of Bosch’s Transforming Missions provides the basis for this discussion. This research is seen as an extension to the thirteen relevant emerging ecumenical paradigms proposed by Bosch. The question of translatability poses the problem question. As the 75% or more Christians in South Africa, we still experience life in the throes of crime, violence, poverty, suffering, rape, abuse of women and children, corruption, murder, xenophobia and the list goes on. The quest is to examine our context in the social analysis, our Christian lives and the churches in the theological analysis. Then to reflect on our context and issues theologically. The researcher believes the crucial point of departure is the Spiritual Formation and Empowerment, which is to bring an impact on the Christian and the church. In so doing reach the 75 % Christian communities for change – the translatability. The need to tie in church and society in reflecting and responding to these contexts would go a long way to bringing change and addressing the issues of the day. This is to unfold in the Pastoral Planning and Praxis as it becomes part of the missional call to work through the paradigms of reconciliation, reconstruction and development for and in the post 1994 South African context. The belief is that a commitment, practice, experience and living out of these three missional paradigms will go some way to answering the translatability question.